Roles of mycobacterium tuberculosis ESAT-6 in the development of renal injury - Gao, Yan-Ting (Int J Clin Exp Med, 2015)
Objective: The present study was designed to evaluate the role of mycobacterium tuberculosis early secretory antigen target-6 (MtbESAT-6) in the development of renal injury. Methods: PET42a (+) ESAT6 prokaryotic expression plasmid was constructed and the purified ESAT6 protein without endotoxin was obtained. Sixty healthy, clean, male Kunming mice were randomly divided into two groups: the experimental group (n = 30) and the control group (n = 30). Each mouse in the experimental group were injected with 0.5 ml ESAT-6 protein, and each mouse in the control group were injected with 0.5 ml sterile saline on the tail vein. Blood, urine and kidney tissues were collected. Serum creatinine (Scr), blood urea nitrogen (BUN), and urinary creatinine (Cr) were determined by HITACHI 7150 automatic biochemical analyzer and creatinine clearance rate (Ccr) was calculated. Renal tissues were conducted for hematoxylin-eosin (HE) staining and pathological scores of renal injury were recorded under the light microscope. Results: Using MTB H37Ra strains genome DNA as template, the ESAT6 gene amplified by Hieff Pfu DNA Polymerase using polymerase chain reaction (PCR) technique was consistent with the expected size. PET42a (+) ESAT6 vector plasmid was successfully obtained and ESAT6 recombinant protein was successfully expressed with the protein concentration of 1.69 mg/ml. BUN and Scr in the experimental group were gradually increased, Ccr was gradually decreased, and the pathological score of renal injury increased gradually, and all of which were significantly higher than that in the control group after the experiment of 12 h, 24 h and 48 h (all P < 0.05). Conclusion: MtbESAT-6 might contribute to the development of renal injury.